ANALISA PERANCANGAN ANTENA OMNI VERTIKAL SEBAGAI TRANSCEIVER PENGUAT ROUTER WIFI DENGAN FREKUENSI 2,4 GHZ - ., Muhammad Hanafi (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
Omnidirectional antenna (Omni) is a type of antenna that has a pattern radiance whole or in all directions in the amount of 360 Â° in the vertical position, as it has a beam thorough omni antenna does not have a coverage area that is too far away, then this antenna is more devoted to relations wireless communication indoors antenna which is paired to a wifi router that functioned as an amplifier reconfigured so this antenna will work as a transceiver amplifier with a working frequency of 2.4 GHz for wireless LAN (local area network). The parameters that must be considered in designing antennas for wireless LAN is working frequency, Input Impedance, SWR (Standing Wave Ratio) and Gain, and omni antenna designed to have input impedance parameter value 34.65 + J 7.24 ohms, the SWR 1.44 and Gain 8.32 dB. In the connectivity test used the command line via the command prompt provided by MS-DOS on a computer with a Windows-based operating system, and testing applications use power beam analyzer wifi version of Android-based smartphones. To test the speed of the download and upload, conducted through speedtest.net on two different networks that wifi.id network with download speeds of 15.22 Mbps, upload 10.48 Mbps network and the Faculty of Engineering at 1.09 Mbps download speed, upload 0.11 Mbps, which is influenced by the speed speedtest maximum value and minimum speeds provided by ISP (internet Service Provider). Keywords : Antena Omni, Transceiver, Router Wifi, frekuensi 2,4 GHz